2015
DOI: 10.1016/j.devcel.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Pax3 and Pax7 Play Essential Safeguard Functions against Environmental Stress-Induced Birth Defects

Abstract: Exposure to environmental teratogenic pollutant leads to severe birth defects. However, the biological events underlying these developmental abnormalities remain undefined. Here, we report a molecular link between an environmental stress response pathway and key developmental genes during craniofacial development. Strikingly, mutant mice with impaired Pax3/7 function display severe craniofacial defects. We show that these are associated with an upregulation of the signaling pathway mediated by the Aryl hydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 67 publications
2
50
0
3
Order By: Relevance
“…However, this study also suggests that neural crest cells arise in the absence of either Pax3 or Pax7. Recently, through Pax3/7 double knockouts and a Pax3 dominant negative, it appears that the function of Pax3/7 are dispensable for mouse neural crest formation (Zalc, Rattenbach, Auradé, Cadot, & Relaix, 2015).…”
Section: Neural Plate Border Specifiersmentioning
confidence: 99%
“…However, this study also suggests that neural crest cells arise in the absence of either Pax3 or Pax7. Recently, through Pax3/7 double knockouts and a Pax3 dominant negative, it appears that the function of Pax3/7 are dispensable for mouse neural crest formation (Zalc, Rattenbach, Auradé, Cadot, & Relaix, 2015).…”
Section: Neural Plate Border Specifiersmentioning
confidence: 99%
“…BSNS is characterized by infiltrative, hypercellular fascicles of bland spindle cells on histologic sections and consistent immunohistochemical positivity for both S100 and smooth muscle actin (SMA). This unique dual phenotype stems from recurrent rearrangements in PAX3 , a transcription factor that normally promotes neural crest and skeletal muscle differentiation[2,3], and is particularly important in the normal development of nasal structures[4]. The original and predominant translocation identified in BSNS is t(2;4)(q35;q31.1), which results in a PAX3-MAML3 fusion protein and activation of PAX3 response elements[5].…”
Section: Introductionmentioning
confidence: 99%
“…PAX7 and PAX3, which are members of the same subgroup of the PAX protein family, play an essential role during craniofacial development (Zalc et al, ). They are critical in the regulation of morphogenesis, survival, patterning, and specification of the frontonasal structures (Mansouri, Stoykova, Torres, & Gruss, ; Wu et al, ; Zalc et al, ). Gene replacement studies in mice have demonstrated the temporal and functional overlap between Pax7 and Pax3 in both embryonic and adult tissue (Relaix, Rocancourt, Mansouri, & Buckingham, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of animal models, complemented by identification of etiological mutations which underlie several human congenital anomalies, have revealed the significance of PAX proteins in craniofacial development and disease (Lang, Powell, Plummer, Young, & Ruggeri, ; Monsoro‐Burq, ; Wang et al, ). The double Pax3/Pax7 knockout mice display a strong frontonasal dysplasia with a fully penetrant frontal cleft (Zalc, Rattenbach, Auradé, Cadot, & Relaix, ). In addition, the persistent Pax3 misexpression in CNC cells results in craniofacial defects, including cleft palate, ocular defects, and perinatal lethality due to inhibitory effects on bone development and formation (Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%